ABCE Proteins: From Molecules to Development - Navarro-Quiles, Carla; Mateo-Bonmatí, Eduardo; Micol, José L. (Frontiers in Plant Science, 2018)
Most members of the large, evolutionarily conserved family of ATP-Binding Cassette (ABC) proteins function as membrane transporters. However, the most evolutionarily conserved group, the ABCE protein subfamily, comprises soluble proteins that were initially denoted RNase L inhibitor (RLI) proteins. ABCE proteins are present in all eukaryotes and archaea and are encoded by a single gene in most genomes, or by two genes in a few cases. Functional analysis of ABCE genes, primarily in Saccharomyces cerevisiae, has shown that ABCE proteins have essential functions as part of the translational apparatus, through their ribosome-dissociating activity. In this review, we summarize the current understanding of ABCE protein function in ribosome biogenesis and recycling, with a particular focus on their known and proposed developmental roles in different species. The ABCE proteins might represent another class of factors contributing to the role of the ribosome in gene expression regulation.